Diabetic autonomic neuropathy of the gastrointestinal tract - Edwin Kuźnik; Robert Dudkowiak; Rajmund Adamiec; Elżbieta Poniewierka (Gastroenterology Review)
Diabetes is a metabolic disease leading to the development of numerous health complications. In developed countries, it is the main cause of blindness, end-stage renal disease, and non-traumatic amputation of the lower limbs. Neuropathy is the most common chronic complication of diabetes. A long-term course of a metabolically unbalanced disease causing damage to the autonomic nervous system of the digestive tract results in the development of many complications, such as intensification of gastro-oesophageal reflux disease, gastroparesis, chronic diarrhoea or faecal incontinence.